Voices from Within-Homemakers as Agents for Social Change - Shu-chuan Liao (Adult Education Research Conference, 2001)
This study is to document how Taiwanese women learned from participating in social action. The focus is on homemakers who are socially marginalized but are involved in private as well as public spheres and speak out on various issues which relate to their everyday lives. The findings suggest that ordinary people can be agents for social change via social movement learning.